2011
DOI: 10.3138/ptc.2010-46
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use among Community-Based Rehabilitation Workers in Bosnia and Herzegovina: A Cross-Sectional Survey

Abstract: Purpose: The Internet may be one way to support and improve rehabilitation practice and service delivery in low-and middle-income countries (LMICs) such as Bosnia and Herzegovina. Little information exists on use of the Internet to enhance the practice and professional development of community-based rehabilitation (CBR) workers in LMICs. The purpose of this study was to assess the patterns of and barriers to Internet use by CBR workers in Bosnia and Herzegovina. Methods: Participants were CBR workers (physioth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The findings on further training in computer and the Internet correspond with previous studies such as Adeleke et al [16] where participants wanted more training in electronic data analysis; Gour & Srivasta [41] with demands on provision for computer training and Cullen [24] with training in the identification, use, and application of evidence in practice. Other corroborating reports are Salako & Tiamiyu [50] on how to enhance efficiency in academic pursuance; Yeung [30] on benefits of technology-enabled training; Ajayi [31] on the introduction of health informatics and Chan et al [51] reported that a group of primary care nurses with consensus required training with a view to improving their computer use.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The findings on further training in computer and the Internet correspond with previous studies such as Adeleke et al [16] where participants wanted more training in electronic data analysis; Gour & Srivasta [41] with demands on provision for computer training and Cullen [24] with training in the identification, use, and application of evidence in practice. Other corroborating reports are Salako & Tiamiyu [50] on how to enhance efficiency in academic pursuance; Yeung [30] on benefits of technology-enabled training; Ajayi [31] on the introduction of health informatics and Chan et al [51] reported that a group of primary care nurses with consensus required training with a view to improving their computer use.…”
Section: Discussionmentioning
confidence: 56%
“…Coit [47] also reported that this constraint was triggered by workload of healthcare providers and Mechanic [48] said that it could be reallocated to make more meaningful communication through the use of the Internet. However, Yeung et al [30] refuted time constraints as an inhibiting factor to care provision, as it was reported to have less influence on Internet use among participants from developing nations relative to their contemporaries in the developed nations. Access to healthcare information has become a key international development issue [49] and improved proficiency in the use of computer and the Internet had been recommended [30] as one way to improve access to invaluable health information among healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among currently available technologies only the Internet has the potential to deliver universal access to up-to-date health care information. The number of Internet users has been dramatically increased worldwide it reaches an estimated 3.89 billion people and this growth has represented a seven fold increase from the year 2000 to 2015 [1]. In the year 2011, about 88% of the US people use the Internet service which is considerably high compared to 55% in the year 2000.…”
Section: Introductionmentioning
confidence: 99%